OPTIMALISASI KINERJA TEKNIS PENGELOLAAN DAERAH IRIGASI SALURAN INDUK MADIUN KABUPATEN MADIUN - Dewi Nusantara, Danayanti Azmi; Damayanti, Nada Devi (Jurnal Teknik Sipil Giratory UPGRIS, 2024)
Ulo Secondary Canal which has an irrigation area of 1,352 ha is one of the secondary canals in the Madiun Main Canal. Ulo Secondary Canal is supplied by three dams namely Semawur Dam, Jati Dam and Gondrok Dam which are located in Madiun Regency. The Madiun Main Canal Irrigation Area has been rehabilitated in 2019, and has been completed in 2022. The Madiun Main Irrigation Channel area is still in need of water. The methods used to calculate water requirements are Climatology Method, FJ. Mock Method, and Water Balance Method. From the calculation, it is known that the condition before rehabilitation, the value of water availability cannot fulfill agricultural water needs in the Ulo Secondary Canal area. In conditions before rehabilitation, the supply from Jati Dam is 18% with a value between 0.43 m3/s - 0.72 m3/s, coupled with water withdrawal at the Semawur Dam intake of 0.06 m3/s and water withdrawal at the Gondrok Dam intake of 0.07 m3/s. The existing water availability can only fulfill the needs of the cropping pattern of paddy (20%) - crops (40%) - crops (45%), with the smallest residual discharge value of 0.09 m3/s in April III. After rehabilitation, the supply value of Jati Dam is 15% with a value between 2.17 m3/s - 2.72 m3/s, with water withdrawal at the Semawur Dam intake of 0.06 m3/s and water withdrawal at the Gondrok Dam intake of 0.07 m3/s.The percentage value after rehabilitation is smaller than before rehabilitation but the value of water supply is bigger. Based on these conditions, several alternative cropping patterns are planned, such as Paddy (100%) - Crops (100%) - Crops (100%), Paddy (100%) - Paddy (100%) - Crops (100%) and Paddy (100%) - Paddy (100%) - Paddy (100%) with a profit amounting to IDR 6,415,515,780.00 in conditions before rehabilitation and after rehabilitation, on alternative III with a cropping pattern of paddy (100%) - paddy (100%) - paddy (100%) obtained the highest profit amounting to IDR 62,144,490,720.00.